Research Productivity of Academics as Reflected in Web of Science: A Scientometric Study - MT, Basavaraja; Kumar, BT Sampath (Journal of Advanced Research in Library and Information Science; Vol 7 No 2 (2020): Journal of Advanced Research in Library and Information Science, 2020)
Research productivity refers to an innovative thoughts and ideas which after theoretical and applied studies lead to publication of articles in leading journals, patent registration or documentation. In this context, the present study aims to identify the research productivity of University of Mysore and Bangalore University during 1989 to 2018. The study also tried to retrieve the information regarding the total number of citations, h-index, average citation per article of the faculty members of University of Mysore and Bangalore University using Web of Science. In order to get the research output of the universities, the search terms ‘University of Mysore’ and ‘Bangalore University’ are entered in the search box of the “Web of Science”. The result of the study shows that 4838 records of the University of Mysore and 2784 records of the Bangalore University have been included in the Web of Science database, out of which, majority (University of Mysore-91.28% and Bangalore University-91.38%) of the records are research articles. The study identified that among the faculty members of University of Mysore, Rangappa has received highest number of citations (4027), followed by Yathirajan hasreceived 2425 citations. Similarly, Kamath faculty member of the Bangalore University has received the highest number of citations (3691), Devi has received 2994 citations.In this context, the study recommends that the faculty members of the both universities need to publish their research articles in peer reviewed journals with high Impact Factor.